Saving graces : finding solace and strength from friends and strangers - Edwards, Elizabeth, 1949- (New York : Broadway Books, 2006)
During the 2004 presidential campaign, Elizabeth Edwards gained admiration for her smart, likable, and down-to-earth personality. These qualities shine forth in this memoir of trials, triumphs, and tragedies, and of the various communities that celebrated her joys and lent her steady strength and quiet hope in darker times. Growing up in a military family, she learned how to make friends easily in new schools and neighborhoods and came to appreciate the unstinting help and comfort naval families shared. Her reminiscences of her years as a mother focus on the support parents offer one another. Her descriptions of her husband's campaigns for Senate, president, and vice president offer a perspective on the groups, great and small, that sustain our democracy. Her fight with breast cancer, which stirred an outpouring of support, has once again affirmed Edwards's belief in the power of community to make our lives better and richer. from the publisher
Keywords: Edwards, Elizabeth, -- 1949-; Edwards, Elizabeth, -- 1949- -- Philosophy; Edwards, John, -- 1953 June 10-; Edwards, John, -- 1953 June 10- -- Family; Legislators$1 (Bspousess -- United States -- Biography; Cancer -- Patients -- United States -- Biography; Lawyers$1 (Bspousess -- North Carolina -- Biography; North Carolina -- Biography